A Media Pharmacology of Face Masks - Yigit Soncul (Media Theory)
During WWII a particular type of face mask was designed for and distributed to children, referred to as ‘Mickey Mouse’ respirators due to their distinctive form and colour. Some of these masks contained asbestos in their filters. Asbestos is a toxic substance that is now banned in over 50 countries. Here we have a case in which a material used for protection from toxicity proves itself to be toxic. In other words, asbestos-filter gas masks function as both remedy and poison – a pharmakon. As such, these masks embody the double logic of the materiality of the media condition, which is advanced in this article through a discussion of the materiality of masks from what I call a media-pharmacological perspective. The article takes asbestos and plastic as key substances that mediate the relationship between the body and its environment in the form of masks. This translates into a discussion of harm and protection within this material register. The substances here provide a link between the material use and politics of masking with its aesthetics.